Testing concrete E-modulus at very early ages through several techniques: an inter-laboratory comparison - Delsaute, Brice (2016)
The design of concrete structures is based on calculation rules, which often do not take into account the very early age behaviour of the material. However, during this period, structural concrete is subjected to strains due to the hydration process of cement. If these strains are restrained by concrete itself or surrounding boundaries, stresses start to build up that can lead to the formation of cracks. Among the parameters involved in the stress build up, the stiffness evolution is of major importance. This paper reports the use of eight different techniques aimed at stiffness evolution assessment, applied on the same concrete mix, in a round robin experimental test within three laboratories. The observations are compared after having expressed the results at the same equivalent age. Both the loading stress rate and amplitude are observed to have an effect of limited importance on the determination of the quasi-static elastic modulus, which might be explained by very short term creep. Ultrasonic measurements provide values of E-modulus that are higher than the values provided by the quasi-static tests at the time of the concrete setting. Similar mechanisms associated to very short term creep could explain the difference between the quasi-static and high-frequency elastic modulus.